Marketing Chain and Quality of Mackerel Tuna (Euthynnus affinis) Landed at Labuan Coastal Fishing Port - Dini Wahyuningsih; Ririn Irnawati; Dini Surilayani (JURNAL PERIKANAN DAN KELAUTAN, 2019)
The highest fish production in Labuan Coastal Fishing Port (LCFP) is mackerel tuna which reached 41,953 ton (22.1%) of total production. Mackerel tuna is economical and perishable commodity. Therefore, it requires a good marketing chain to maintain its quality. The purpose of this research is to determine the marketing chain of mackerel tuna landed at LCFP; determine the marketing margins of each marketing agent; and analyze the quality of mackerel tuna from unloading ship to the consumer. This research was conducted in March-April 2019 at LCFP. This study used the survey method. While the methods used for quality testing of tuna are sensory (visual observations) or by organoleptic tests by parameters in the form of eye conditions, gills, meat and odor texture of fresh fish standards using a score sheet based on BSN. Checking the quality of fish is done at every marketing chain. Data analysis was carried out descriptively. The result show that there are four types of marketing chains in LCFP. The highest marketing margin obtained by outside trades (IDR 5,000 or 20%) on the fourth channel and the lowest margin sales obtained by main collectors on the second and third channels (IDR 2,000 or 8%). The longer the marketing chain, the lower the quality of mackerel tuna.